Art-Pedagogical Means of Forming Professional Competence of the Future Specialists - Rudenka, Tetiana (Pedagogical Discourse, 2014)
On the basis of the analysis of dinamic model of teaching by K.Fopel the goals and the content of art-pedagogical means of professional preparation have been offered in the article; the influence of art-pedagogics over the motivational, reflexive and personal components of professional competence of the future specialists has been grounded; the stages of application of art-pedagogical means in the process of professional preparation have been determined and characterized; the content of artistic, theatrical, literary, efferent, collective creative work of students of a college has been revealed.